The Institutional Effects on Strategic Alliance Partner Selection in Transition Economies: China vs. Russia - Hitt, Michael A.; Ahlstrom, David; Dacin, M. Tina; Levitas, Edward; Svobodina, Lilia (Organization Science, 2004)
China and Russia represent major economies in transition from command economies, yet their paths to the market have differed greatly. Their divergent approaches have helped create distinct institutional environments. This study focuses on a particularly important strategic decision firms face—alliance partner selection. The study's results suggest that China's more stable and supportive institutional environment has helped Chinese firms take a longer-term view of alliance partner selection, focusing more on the potential partner's intangible assets along with technological and managerial capabilities. In contrast, the less stable Russian institutional environment has influenced Russian managers to focus more on the short term, selecting partners that provide access to financial capital and complementary capabilities so as to enhance their firms—ability to weather that nation's turbulent environment. This study contributes to knowledge about the influence of the institutional environment on alliance partner selection decisions for firms domiciled in transition (and emerging) economies.